2000
DOI: 10.1159/000053993
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid DNA Vaccines: Investigation of Integration into Host Cellular DNA following Intramuscular Injection in Mice

Abstract: The primary safety concern for DNA vaccines is their potential to integrate into the host cell genome. We describe an integration assay based on purification of high-molecular-weight genomic DNA away from free plasmid using gel electrophoresis, such that the genomic DNA can then be assayed for integrated plasmid using a sensitive PCR method. The assay sensitivity was approximately 1 plasmid copy/µg DNA (representing ∼150,000 diploid cells). Using this assay, we carried out integration studies of three differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
131
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(138 citation statements)
references
References 22 publications
7
131
0
Order By: Relevance
“…Frozen mice tissues were homogenized and divided into aliquots of about 20 mg, and total DNA was purified from an aliquot of the homogenate by boiling, 16 phenol-chloroform extraction 17 and DNA isolation kit. Briefly, for the boiling method, cell suspensions of different tissues were washed by PBS three times and suspended in 100 ml sterile ddH2O.…”
Section: Construction Of Standard Curves For Pcn Determinationmentioning
confidence: 99%
“…Frozen mice tissues were homogenized and divided into aliquots of about 20 mg, and total DNA was purified from an aliquot of the homogenate by boiling, 16 phenol-chloroform extraction 17 and DNA isolation kit. Briefly, for the boiling method, cell suspensions of different tissues were washed by PBS three times and suspended in 100 ml sterile ddH2O.…”
Section: Construction Of Standard Curves For Pcn Determinationmentioning
confidence: 99%
“…Animal studies involving plasmid DNA injections have shown that mutations from a potential integration event would be extremely infrequent, about 3000 times lower than the spontaneous mutation rate for mammalian genomes. [16][17][18] However, in the case of DNA vaccination against foreign antigens, it is of some concern that transfected muscle cells may be attacked and injured by the immune system, and this has been reported. 4,7,8 A related concern is the production of pathogenic anti-DNA antibodies, potentially induced by plasmid DNA and its immunostimulatory sequences (ISS), but the risk appears relatively small.…”
Section: Potential Hazardsmentioning
confidence: 99%
“…This appears to happen at a low frequency. 16,17 However, we will see in this review that the resultant integrated structure can be surprisingly complex and unpredictable compared to the expected structure of targeted integration, making it difficult to evaluate the risks inherent in these events (see Figure 1).…”
Section: Introductionmentioning
confidence: 99%